1989
DOI: 10.1111/j.1348-0421.1989.tb01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method for Quantitation of Cell‐Bound Protein A on Staphylococcus aureus Cells by Means of Hemagglutination with Sheep Erythrocytes Differentially Sensitized with Rabbit Antibody and Its Clinical Application

Abstract: A simple method for quantitation of cell-bound protein A (SpA) on organisms of Staphylococcus aureus was successfully devised by using hemagglutination between staphylococcal organisms and a series of sheep erythrocyte suspensions sensitized with different amounts of and sheep erythrocyte rabbit antiserum. The validity of the principle and the reproducibility of the method presented here were precisely analyzed and the details of the method are presented. The hemagglutination was quantitatively inhibited both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…I t is interesting that SpA-bearing strain is rare in bovines of which immunoglobulins have low affinity to SpA (9). Recently, it was reported that over twothirds of S. aureus strains isolated from clinical materials bear no or a trace amount of cell-bound SpA (11). Since S. aureus are equipped with many other mechanisms for the adhesion to host cells, S. aureus might adhere to various host tissues and cells, according to the immunological state of the host and its location in the host by the most suitable binding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…I t is interesting that SpA-bearing strain is rare in bovines of which immunoglobulins have low affinity to SpA (9). Recently, it was reported that over twothirds of S. aureus strains isolated from clinical materials bear no or a trace amount of cell-bound SpA (11). Since S. aureus are equipped with many other mechanisms for the adhesion to host cells, S. aureus might adhere to various host tissues and cells, according to the immunological state of the host and its location in the host by the most suitable binding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Winblad and Ericson (14) reported the availability of hemagglutination test for the detection of cell-wall-binding SpA of S. aureus and its quantitative version has been devised in our laboratory (4). In the present investigation, the hemagglutination method was applied for the detection of SpA contained in E. coli transformants.…”
Section: Discussionmentioning
confidence: 99%
“…The Cowan strain which is known to be a good protein A producer was used as a positive control (5). The titer of protein A was expressed as 2 <nl) where n=well number showing haemagglutination.…”
Section: Protein a Titresmentioning
confidence: 99%